Instrument constituencies and transnational policy diffusion: the case of conditional cash transfers - Béland, D.; Foli, R.; Howlett, M.; Woo, J.J. (Routledge, 2018)
The purpose of this paper is to improve knowledge of the transnational diffusion of public policies. It argues that existing studies on the subject do not provide an adequate understanding of the mechanisms through which diffusion takes place, nor do they sufficiently address the roles specific organizations and individuals play in driving or determining the policy transfer process. We address these shortcomings by studying the diffusion of conditional cash transfer (CCT) programmes from Latin America to Ghana and the Philippines over the past decade. We use the concept of ‘instruments constituency’ to delineate and trace the various actors and channels involved in the diffusion of CCTs. The comparative case studies show that these constituencies, dedicated to the articulation, adoption, and expansion of particular policy instruments, are central players in transnational diffusion of policies. This finding has significant implications for the study of policy transfer and diffusion, identifying a heretofore neglected actor in these processes. © 2018 Informa UK Limited, trading as Taylor & Francis Group
Keywords: conditional cash transfers; Ghana; instrument constituencies; Philippines; policy actors; Policy diffusion